2006
DOI: 10.1021/ja061014t
|View full text |Cite
|
Sign up to set email alerts
|

Selective DNA Strand Scission with Binuclear Copper Complexes:  Implications for an Active Cu2−O2 Species

Abstract: A homologous series of binuclear copper(II) complexes [Cu II 2 (Nn)(Y) 2 ] 2+ (1-3) (n = 3-5 and Y = (ClO 4 ) − or (NO 3 ) − ) were studied to investigate the intermediate(s) responsible for selective DNA strand scission in the presence of MPA/O 2 (MPA = 3-mercaptopropanoic acid). While the N3 complex does not react, the N4 and N5 analogues show comparable activity with strand scission occurring at a single-strand/double-strand junction. Identical reactivity is also observed in the alternate presence

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 35 publications
1
74
0
1
Order By: Relevance
“…The significant increase in the DNA cleavage activity by 2 in the presence of H 2 O 2 and the inhibition of activity in the presence of DMSO and KI suggest that this reaction is preferentially proceeding by a hydroxy radical mechanism with · OH and hydrogen peroxide species. The oxidative reaction pathway observed here has been suggested previously in the vast majority of DNA cleavage activity by copper complexes [14,15,48,[51][52][53][54][55][56] and in the DNA photocleavage activity by some cobalt(III) complexes. [57] The rate enhancement for DNA cleavage by 2 or its hydrolytic active species [Cu 2 (μ-bdpaT Cl )(H 2 O) 3 Cl] 3+ corresponding to a 2.5 ϫ 10 6 fold increase over the noncatalyzed DNA (k = 1.0 ϫ 10 -11 s -1 at 37°C) [58] reveals the efficiency of this complex to cleave DNA.…”
Section: Cleavage Of Plasmid Dna By 1 Andsupporting
confidence: 65%
“…The significant increase in the DNA cleavage activity by 2 in the presence of H 2 O 2 and the inhibition of activity in the presence of DMSO and KI suggest that this reaction is preferentially proceeding by a hydroxy radical mechanism with · OH and hydrogen peroxide species. The oxidative reaction pathway observed here has been suggested previously in the vast majority of DNA cleavage activity by copper complexes [14,15,48,[51][52][53][54][55][56] and in the DNA photocleavage activity by some cobalt(III) complexes. [57] The rate enhancement for DNA cleavage by 2 or its hydrolytic active species [Cu 2 (μ-bdpaT Cl )(H 2 O) 3 Cl] 3+ corresponding to a 2.5 ϫ 10 6 fold increase over the noncatalyzed DNA (k = 1.0 ϫ 10 -11 s -1 at 37°C) [58] reveals the efficiency of this complex to cleave DNA.…”
Section: Cleavage Of Plasmid Dna By 1 Andsupporting
confidence: 65%
“…Oxidative cleavage of DNA by metal complexes can be achieved in the presence of external reagents, while common reductant were ascorbic acid, mercaptopropionic acid (MPA), polyphenol and S(IV) complexes (Patwardhan and Cowan 2001;Jin and Cowan 2005;Lainé et al 2004;Thyagarajan et al 2006;Alipázaga et al 2008). Recent report from our laboratory has shown that 1, 10-phenanthroline/Lthreonine copper (II) complexes with chlorogenic acid as biological reductant can induce DNA oxidative damage (Wang et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Among several types of transition metal complexes used as synthetic hydrolases, copper(II) and zinc(II) complexes are better suited for the hydrolysis of DNA due to the strong Lewis acid properties of these metal ions. Transition metal complexes containing polypyridylamine-derived ligands have been developed as artificial nucleases, and they displayed versatile DNA cleavage properties in the absence or presence of a redox agent [11][12][13][14][15]. For example, Karlin group [11] has reported a dicopper complex [Cu II 2 (PD 0 O)(H 2 O) 2 ](ClO 4 ) 3 Á2H 2 O (PD 0 O H = 4-tert-butyl-2,6-bis[bis(2-pyridylethyl)-amino]phenol) that predominantly effects DNA base (rather than ribose) oxidation on G residues in single-stranded regions of DNA.…”
Section: Introductionmentioning
confidence: 99%